2015
DOI: 10.1089/brain.2014.0251
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Functional Connectivity of Brain Networks and Their Dynamic Interaction in Temporal Lobe Epilepsy

Abstract: This study presents a cross-sectional investigation of functional networks in temporal lobe epilepsy (TLE) as they evolve over years of disease. Networks of interest were identified based on a priori hypotheses: the network of seizure propagation ipsilateral to the seizure focus, the same regions contralateral to seizure focus, the cross hemisphere network of the same regions, and a cingulate midline network. Resting functional magnetic resonance imaging data were acquired for 20 min in 12 unilateral TLE patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 47 publications
(63 reference statements)
7
61
0
Order By: Relevance
“…The network structure in TLE appears to also undergo progression and reorganization over time [41]. Prior work using seed based functional connectivity analysis has revealed reduced functional independence of the presumed ipsilateral ictal network from midline networks in TLE [42], which may also indicate progressive homogenization (less independence) over time using a different analysis approach. This reduced independence may also be the reason for the observed progressive increase in cross-hippocampal connectivity with longer duration in TLE [43].…”
Section: Discussionmentioning
confidence: 99%
“…The network structure in TLE appears to also undergo progression and reorganization over time [41]. Prior work using seed based functional connectivity analysis has revealed reduced functional independence of the presumed ipsilateral ictal network from midline networks in TLE [42], which may also indicate progressive homogenization (less independence) over time using a different analysis approach. This reduced independence may also be the reason for the observed progressive increase in cross-hippocampal connectivity with longer duration in TLE [43].…”
Section: Discussionmentioning
confidence: 99%
“…of altered functional organization varying with age of seizure onset has been demonstrated through rsFC [4,21,22]. A recent study by Morgan et al [21] showed that there is an initial disruption of cross-hemispheric networks and an increase in static functional connectivity in the ipsilateral temporal network accompanying the onset of TLE seizures.…”
Section: Key Pointsmentioning
confidence: 99%
“…A recent study by Morgan et al [21] showed that there is an initial disruption of cross-hemispheric networks and an increase in static functional connectivity in the ipsilateral temporal network accompanying the onset of TLE seizures. As seizures progress over years, functional connectivity declines within both a static ipsilateral network and a dynamic midline (e.g., cingulate) network; however, these networks appear to be independent of each other.…”
Section: Key Pointsmentioning
confidence: 99%
“…Such metrics have been demonstrated as promising biomarkers for distinguishing between states 27,29 , or between patients and healthy controls 6164 .…”
Section: Summarizing Brain Dynamicsmentioning
confidence: 99%
“…Investigators have pursued DFC methods in a wide variety of brain disorders, including schizophrenia 38,131,132133134 , bipolar disorder 131 , autism spectrum disorder 135,136 , major depression, mild cognitive impairment 137138 , Alzheimer’s disease 139 and dementia with Lewy bodies 95 , post-traumatic stress disorder 78 , epilepsy 61,140 and multiple sclerosis, among others 79 . Encouragingly, these studies have begun to suggest that dynamic features are more sensitive or specific than static connectivity in differentiating between healthy and control populations.…”
Section: Figurementioning
confidence: 99%